A bacterial hemerythrin-like protein MsmHr inhibits the SigF-dependent hydrogen peroxide response in mycobacteria - Li, Xiaojing; Tao, Jun; Hu, Xinling; Chan, John; Xiao, Jing; Mi, Kaixia (Frontiers in Microbiology, 2015)
Hydrogen peroxide (H2O2) is one of a variety of reactive oxygen species (ROS) produced by aerobic organisms. Host production of toxic H2O2 in response to pathogen infection is an important classical innate defense mechanism against invading microbes. Understanding the mechanisms by which pathogens, in response to oxidative stress, mediate defense against toxic ROS, can reveal anti-microbial targets and shed light on pathogenic mechanisms. In this study, we provide evidence that a Mycobacterium smegmatis hemerythrin-like protein MSMEG_2415, designated MsmHr, is a H2O2-modulated repressor of the SigF-mediated response to H2O2. Circular dichroism and spectrophotometric analysis of MsmHr revealed properties characteristic of a typical hemerythrin-like protein. An msmHr knockout strain of M. smegmatis mc2155 (ΔmsmHr) was more resistant to H2O2 than its parental strain, and overexpression of MsmHr increased mycobacterial susceptibility to H2O2. Mutagenesis studies revealed that the hemerythrin domain of MsmHr is required for the regulation of the H2O2 response observed in the overexpression study. We show that MsmHr inhibits the expression of SigF (MSMEG_1804), an alternative sigma factor that plays an important role in bacterial oxidative stress responses, including those elicited by H2O2, thus providing a mechanistic link between ΔmsmHr and its enhanced resistance to H2O2. Together, these results strongly suggest that MsmHr is involved in the response of mycobacteria to H2O2 by negatively regulating a sigma factor, a function not previously described for hemerythrins.